Finerenone in Patients with Chronic Kidney Disease and Type 2 Diabetes: The FIDELIO-DKD Subgroup from China - Haitao Zhang; Jingyuan Xie; Chuanming Hao; Xuemei Li; Dalong Zhu; Hongguang Zheng; Xudong Xu; Zhaohui Mo; Weiping Lu; Yibing Lu; Chaoqing Wu; Nanwei Tong; et al. (Karger Publishers, 2023)
Background: This prespecified subgroup analysis of the FIDELIO-DKD trial aimed to evaluate the efficacy and safety of finerenone in patients with chronic kidney disease (CKD) and type 2 diabetes mellitus (T2DM) in China. Methods: 372 participants were recruited from 67 centers in China and randomized 1:1 to oral finerenone or placebo with standard therapy for T2DM. The primary composite outcome included kidney failure, sustained decrease of estimated glomerular filtration rate ≥40% from baseline over at least 4 weeks, or renal death. The key secondary composite outcome included death from cardiovascular causes, nonfatal myocardial infarction, nonfatal stroke, or hospitalization for heart failure. Results: After a median follow-up of 30 months, the finerenone group showed a relative risk reduction (RRR) of 41% (hazard ratio [HR] = 0.59, 95% confidence interval [CI], 0.39-0.88; p = 0.009) for the primary composite outcome compared with placebo, consistent across its components with treatment benefits with finerenone. Based on an absolute between-group difference of 12.2% after 30 months, the number of patients who needed to be treated with finerenone to prevent one primary outcome event was eight (95% CI: 4-84). For the key secondary composite outcome, the finerenone group showed a RRR of 25% (HR = 0.75, 95% CI, 0.38-1.48; p = 0.408). Adverse events were similar between the two groups. The effects of finerenone on blood pressure were modest. No gynecomastia events were reported in the study. Hyperkalemia leading to discontinuation occurred in eight (4.3%) and two (1.1%) participants in the finerenone and control groups, respectively. The incidence of acute kidney injury was comparable between the two groups (1.6% vs. 1.6%). Conclusions: Finerenone resulted in lower risks of CKD progression than placebo and a balanced safety profile in Chinese patients with CKD and T2DM.